Inertial Support Capacity Analysis and Equivalent Inertia Estimation of Wind Turbines in Integrated Inertial Control - ZHOU Tao, HUANG Ju, HAN Rushuai, HU Qinran, QUAN Hao (Shanghai Jiaotong Daxue xuebao)
In response to the new power system frequency safety issues caused by the high percentage of renewable energy sources connected to the grid, wind turbines mostly use integrated inertia control for the inertia and primary frequency regulation support provided by the power system. In order to better improve the inertia safety of the system and guarantee the grid frequency stability, dynamic modeling of wind turbines with integrated inertia control is conducted to derive the effective inertia of the wind turbine based on the kinetic energy contained in the wind turbine and the frequency support it provides to the grid. Then, a system frequency response model of the wind turbine in integrated inertia control is established, the analytical formula of the effective inertia time constant in the process of wind turbine frequency regulation is obtained, and the inertia support capability is analyzed. Based on the “equal area principle”, the equivalent inertia evaluation method of the wind turbine in integrated inertia control is derived, which can analyze the inertial support capacity provided by the wind turbine and give quantitative results. Finally, the validity and feasibility of the proposed method is verified in a case study, and the impact of different factors on the equivalent inertia of the wind turbine is analyzed.